Safety of hydroxychloroquine and darunavir or lopinavir in COVID-19 infection. (21st November 2020) - Meriglier, Etienne; Rivoisy, Claire; Hessamfar, Mojgan; Bernard, Noelle; Aureau, Ines; Lapoirie, Joelle; Contis, Anne; Sacher, Frédéric; Sacristan, Benjamin; Lahouati, Marin; Pedeboscq, Stéphane; Vandenhende, Marie-Anne; et al.
Abstract: Background: Combination therapy with hydroxychloroquine and darunavir/ritonavir or lopinavir/ritonavir has been suggested as an approach to improve the outcome of patients with moderate/severe COVID-19 infection. Objectives: To examine the safety of combination therapy with hydroxychloroquine and darunavir/ritonavir or lopinavir/ritonavir. Methods: This was an observational cohort study of patients hospitalized for COVID-19 pneumonia treated with hydroxychloroquine and darunavir/ritonavir or lopinavir/ritonavir. Clinical evaluations, electrocardiograms and the pharmacokinetics of hydroxychloroquine, darunavir and lopinavir were examined according to clinical practice and guidelines. Results: Twenty-one patients received hydroxychloroquine with lopinavir/ritonavir (median age 68 years; 10 males) and 25 received hydroxychloroquine with darunavir/ritonavir (median age 71 years; 15 males). During treatment, eight patients (17.4%) developed ECG abnormalities. Ten patients discontinued treatment, including seven for ECG abnormalities a median of 5 (range 2–6) days after starting treatment. All ECG abnormalities reversed 1–2 days after interrupting treatment. Four patients died within 14 days. ECG abnormalities were significantly associated with age over 70 years, coexisting conditions (such as hypertension, chronic cardiovascular disease and kidney failure) and initial potential drug interactions, but not with the hydroxychloroquine concentration. Conclusions: Of the patients with COVID-19 who received hydroxychloroquine with lopinavir or darunavir, 17% had ECG abnormalities, mainly related to age or in those with a history of cardiovascular disease.